Novel Mutations in AKT1 Gene in Prostate Cancer Patients in Jordan - Ala’a Alasmar; Zina Al-Alami; Sima Zein; Asmaa Al-Smadi; Samir Al Bashir; Mohammed S. Alorjani; Raed M. Al-Zoubi; Mazhar Al Zoubi (Current Issues in Molecular Biology)
The AKT1 oncogene is related to various cancers due to its critical role in the PIC3CA/AKT1 pathway; however, most of the studies screened the hotspot mutation AKT1 (E17K) with various incidences. Low frequency or lack of AKT1 (E17K) mutation was reported in prostate cancer (PC) patients. This study aims to explore genetic alterations in the AKT1 PH domain by extending the sequencing to include AKT1 gene exons 3 and 4. Genomic DNA was extracted from 84 Formalin-Fixed Paraffin-Embedded samples of PC patients in Jordan, and then subjected to PCR and sequencing for the targeted exons. This study revealed the presence of two novel mutations (N53Y and Q59K) and a high frequency of mutations in exon 4, with a lack of mutations in the E17K hotspot. Nine missense and two synonymous mutations were detected in exon 4 (Phe27Tyr, Phe27Leu, Ala58Thr, Ser56Phe, Arg41Trp, Phe35Leu, Asp32Glu, Phe35Tyr, and Gln43Lys) and (Ser56 and Glu40), respectively. Two synonymous mutations were detected in exon 3 (Leu12 and Ser2). It is concluded that there is a high frequency of AKT1 mutation in PC patients in Jordan with two novel missense mutations in the Pleckstrin homology (PH) domain. E17K hotspot mutation was not detected in any tested samples, which underlined the significant role of mutations in other AKT1 exons in PC development.